Forensic Toxicology Analysis of Suicidal Hanging Deaths in Eastern Province-Saudi Arabia - Naglaa F. Mahmoud; Maha K. Al-Mazroua; Moustafa M.Afify; Sahar Y. Issa (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Suicide is a multifaceted phenomenon with multiple underlying risk factors, including alcoholand/or abuse of other drugs and psychiatric illnesses. Toxicological analysis is of crucial importance even inhanging deaths where the cause of death seems to be ‘obvious’. Objective: To investigate hanging suicidedeaths, focusing on toxicological findings in their postmortem specimens, over a period of six years in theEastern Province, Saudi Arabia. Methods: The suicidal hanging deaths in the period from 2014 to 2019were retrospectively studied from autopsy and toxicology analysis reports. Results: Of the investigated 75hanging suicides, 64 (85.3%) were males and 11 (14.7%) were females. Most of the cases were in the agegroup between 31 and 40 years of age (36%). Non-Saudi nationals (57, 76%) much prevailed over Saudipeople (18, 24%) and the highest is the Indian population (27, 36%), followed by Saudi nationals (18, 24%).Ethanol was the commonest detected substance in the studied specimens (45, 60%). Cannabis ranked thesecond (14, 18.6%) followed by antipsychotic drugs (10, 13.3%) and amphetamine (7, 9. 3%).Conclusion:The precise statistical mortality database for hanging suicides deaths may provide a valuable evidence forthe importance of postmortem toxicology analysis and the role of alcohol and its effect on the aggressivebehavior, human health and mortality. In the current study, Ethanol was the highest detected substance in thestudied specimens (45, 60%), with predominance of non-Saudi Indian males.